Genetics of foraging behavior of the predatory mite, Phytoseiulus persimilis - Konakandla, Bhanu S. (Kansas State University, 2006)
Phytoseiulus persimilis (Acari: Phytoseiidae) is a specialist predator on tetranychid mites, especially on the twospotted spider mite, Tetranychus urticae Koch (Acari: Tetranychidae). The foraging environment of the predatory mites consists of prey colonies distributed in patches within and among plants. Quantitative genetic studies have shown genetic variation in, and phenotypic correlations among, several foraging behaviors within populations of the predatory mite, P. persimilis. The correlations between patch location, patch residence, consumption and oviposition imply possible fitness trade-offs. We used molecular techniques to investigate genetic variation underlying the foraging behaviors. However, these genetic studies require a sufficiently large amount of DNA which was a limiting factor in our studies. Therefore, we developed a method for obtaining DNA from a single mite by using a chelex extraction followed by whole genome amplification. Whole genome amplification from a single mite provided us with a large quantity of high-quality DNA. We obtained more than a ten thousand-fold amplified DNA from a single mite using 0.01ng as template DNA. Sequence polymorphisms of P. persimilis were analyzed for nuclear DNA Inter Transcribed Spacers (ITS1 & ITS2) and for a mitochondrial 12S rRNA. The sequence comparisons among individuals identified a number of polymorphisms in the 12S sequences. The foraging gene (for) associated with rover-sitter behavioral strategies of Drosophila is known to have role in feeding behaviors of honeybee and other arthropods. We surmised that the same or a similar gene may be present in P. persimilis. Among the foraging behavior(s) exhibited by this predatory mite, we were particularly interested in resource/prey-dependent dispersal behavior. We isolated a partial sequence that is presumed to be the orthologue of the foraging (for) gene. We named the putative foraging gene as Ppfor (for Phytoseiulus persimilis foraging gene). We used a fragment of Ppfor gene as a molecular marker between populations and among individuals and, further, to help understand behavioral phenotypes.
Keywords: Phytoseiulus persimilis; foraging behavior; molecular markers; foraging gene; Biology, Entomology (0353); Biology, Genetics (0369); Biology, Molecular (0307)